Analysis of the Influence of Governance, Audit Opinions and KAP Audits on the Performance of Companies Listed on the Indonesian Stock Exchange in 2017-2021 - Kerorin Kerorin (Universitas Internasional Batam, 2024)
This research is able to provide a foundation for the purpose of analyzing the influence of corporate governance, audit opinions and KAP audits on company performance. Corporate governance assessment variables include board size, audit committee, meeting frequency, and managerial ownership. The company's performance variable is measured by earnings per share (EPS). The population formed in this study is a company listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2021 with the number referring to the sample with a score of 2,152 data. Financial and annual reports published on www.idx.co.id are mined for information. Purposive sampling was used, in which a representative sample was selected at random considering a number of factors. Overall, data from 777 different businesses were collected. SPSS and Eviews will be used to perform panel regression data analysis on the available data. The results obtained from the research interpret that there is a significant positive influence on the variables of the board of directors, meeting frequency, managerial ownership, audit opinion and KAP size on other performance as well as on audit committee variables that do not have a significant effect on performance.